Protocadherin 11X/Y a human-specific gene pair: an immunohistochemical survey of fetal and adult brains. - Priddle, T; Crow, T (2013)
Protocadherins 11X and 11Y are cell adhesion molecules of the δ1-protocadherin family. Pcdh11X is present throughout the mammalian radiation; however, 6 million years ago (MYA), a reduplicative translocation of the Xq21.3 block onto what is now human Yp11 created the Homo sapiens-specific PCDH11Y. Therefore, modern human females express PCDH11X whereas males express both PCDH11X and PCDH11Y. PCDH11X/Y has been subject to accelerated evolution resulting in human-specific changes to both proteins, most notably 2 cysteine substitutions in the PCDH11X ectodomain that may alter binding characteristics. The PCDH11X/Y gene pair is postulated to be critical to aspects of human brain evolution related to the neural correlates of language. Therefore, we raised antibodies to investigate the temporal and spatial expression of PCDH11X/Y in cortical and sub-cortical areas of the human fetal brain between 12 and 34 postconceptional weeks. We then used the antibodies to determine if this expression was consistent in a series of adult brains. PCDH11X/Y immunoreactivity was detectable at all developmental stages. Strong expression was detected in the fetal neocortex, ganglionic eminences, cerebellum, and inferior olive. In the adult brain, the cerebral cortex, hippocampal formation, and cerebellum were strongly immunoreactive, with expression also detectable in the brainstem.